Cultural Policy is Local Understanding Cultural Policy as Situated Practice - Durrer, Victoria; Gilmore, Abigail; Jancovich, Leila; Stevenson, David (New Directions in Cultural Policy Research, 2023)
This Open Access edited collection calls for a greater understanding of 'the local' within the ways the arts, culture and creative practices are governed, promoted, regulated, resourced and valued. Cultural policy studies tends to privilege the national (and international) as the primary site at which cultural policy is enacted, and focuses on the 'local' as a case study of practice, rather than a site of policy in its own right. While this may make global policy transfer manageable for national policy agencies, it ignores the contingent relationships, diverse geographies and distinct identities of localities. This volume addresses this gap and is structured around three themes: disciplining the local, which examines key concepts from different academic fields of study; managing the local, which identifies policy approaches that engage with the idea of 'the local' in different ways; and practising the local, which offers case studies of how 'local' cultural policies are being enacted in places of differing scale and geography.